Standardisation of Avipattikar Churna- A Polyherbal Formulation - Aswatha Ram HN; Kaushik Ujjwal; Lachake Prachiti; Shreedhara CS (Pharmacognosy Research, 2009)
Standardisation of herbal formulation is essential in order to assess the quality of drugs, based on the concentration of their active principles. The present paper reports on standardisation of Avipattikar churna, a poly herbal ayurvedic medicine used as remedy for acidity and complications associated with it like headache, nausea and vomiting. It is also used as laxative and helps to increase appetite. Avipattikar churna was prepared as per Ayurvedic Formulary of India. In-house preparation and two marketed have been standardised on the basis of organoleptic characters, physical characteristics and physico-chemical properties. The set parameters were found to be sufficient to evaluate the churna and can be used as reference standards for the quality control/quality assurance laboratory of a Pharmaceutical house.
Keywords: Avipattikar churna; Physicochemical parameters; Polyherbal formulation; Standardisation